2023
DOI: 10.1155/2023/3239960
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Alloimmunization and Autoimmunization in Blood Transfusion-Dependent Sickle Cell Disease and β-Thalassemia Patients in Al-Ahsa Region, Saudi Arabia

Abstract: Introduction. The risk of developing transfusion-related complications, especially alloimmunization, is an ongoing concern for transfusion-dependent patients. It is important to determine the rate of alloimmunization and autoimmunization in Al-Ahsa Region, Saudi Arabia, where sickle cell disease (SCD) and thalassemia incidence rates are the highest in Saudi Arabia. Methods. A cross-sectional study was conducted to review the transfusion history of patients with SCD and thalassemia at the King Fahad Hospital (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
4
2
Order By: Relevance
“…Another study in 2023 from Al-Hasa, eastern region of Saudi Arabia, reported 16.7% alloimmunization for SCD patients and 11.97% alloimmunization for thalassemia patients. 12 The rate of alloimmunisation reported from the latter two studies from the western region is significantly higher when compared to our study. 12 , 14 High alloimmunisation rates reported previously from Jazan region 21 might be due to the fact that the study was from single center and had lower sample size than the current study.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Another study in 2023 from Al-Hasa, eastern region of Saudi Arabia, reported 16.7% alloimmunization for SCD patients and 11.97% alloimmunization for thalassemia patients. 12 The rate of alloimmunisation reported from the latter two studies from the western region is significantly higher when compared to our study. 12 , 14 High alloimmunisation rates reported previously from Jazan region 21 might be due to the fact that the study was from single center and had lower sample size than the current study.…”
Section: Discussioncontrasting
confidence: 79%
“… 12 The rate of alloimmunisation reported from the latter two studies from the western region is significantly higher when compared to our study. 12 , 14 High alloimmunisation rates reported previously from Jazan region 21 might be due to the fact that the study was from single center and had lower sample size than the current study. 21 In addition, the differences from the other in these studies in Saudi Arabia could be attributed to the diverse ethnic backgrounds of the donor and recipient populations and multiple transfusion of non-phenotypically matched blood units, which are both known to be associated with an increased risk of alloimmunisation in transfusion-dependent patients.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Transfusions help treat or prevent the perioperative complications, acute chest syndrome, and acute anemia associated with SCD; however, blood transfusions can also cause side effects such as alloimmunization and iron overload. Even though various strategies are employed to help mitigate these side effects, such as chelators for treating iron overload and antigen matching for preventing alloimmunization, these side effects persist [21,22].…”
Section: Blood Transfusionsmentioning
confidence: 99%